The Solution of Hotel Business with the Concept of A Learning Organization - Pornleartkochakorn, Nantawat; Limsiritong, Karnjira; Santisarn, Burin; Limsiritong, Thanapum (Siam University Journal of Business Administration, 2022)
At present, the hotel business has been severely affected by both internal and external factors. The internal factors include, for instance, capital turnover, competence skills of employees to be developed, and information technology systems within the organization. The external factors include, for instance, natural disasters, rapid changes due to globalization, events of political turmoil, changes in consumer behavior, rapid technology changes, competition in industry, and disease such as the COVID-19 situation. The Covid-19 has created a vast negative impact and greatly affected the hotel business since January 2020 until now. The problem of COVID-19 has caused changes in way of living and business operation in new forms, known as New Normal. The hotel business has to adjust the business method to be in line with the situation that arises. By establishing measures, guidelines and policies, so the concept of a learning organization is one concept that allows the organization to adapt to the changing environment. In this article, the concept of a learning organization is presented. The article also presents guidelines for the overall adjustment of the hotel business. Policies and measures that the hotel should implement for the adjustment mainly come from the process of being a learning organization. However, to get through the crisis, learning, developing, disseminating knowledge throughout the organization needs willing and helpful cooperation from the entire organization.